It takes more than agency: Linking support from teaching staff, career engagement, and movement capital among university students - Petruzziello, Gerardo; Antonio, Audrey Ansay; Chiesa, Rita; Mariani, Marco Giovanni (Frontiers in Psychology, 2022)
Career self-management behaviours are key to overcoming the challenges of entry into the labour market. Combining the Conservation of Resources and Career Self-management theories, this study delves into the concept of Career Engagement among Italian University students by examining its relationship with Support from teaching Staff and Movement Capital. We hypothesised a mediation model in which Support from Teaching Staff predicts Career Engagement which, in turn, fosters Movement Capital. As the pandemic led to the adoption of online learning solutions, we also explored whether and how the interaction between teachers and students during online classes moderates the said mediation relationship. We collected data from 276 Italian University students through an online questionnaire. Results supported the mediation hypothesis, corroborating the mediating role of Career Engagement. We also observed that this relationship is stronger at medium and higher levels of online interaction between teachers and students. Findings contribute to existing evidence about the role of Career Engagement in facilitating career resources' acquisition and extend the understanding of its contextual antecedents in Higher Education contexts. Results also align with the importance attributed to interaction in online learning environments. This work suggests ways to encourage career behaviours in Higher Education and equip prospective labour market entrants with career resources.